Zero-valent iron nanomaterial Fe0@Fe2MnO4 for ultrasensitive electroanalysis of As(iii): Fe0 influenced surficial redox potential. Issue 11 (11th January 2021) - Yang, Meng; Xie, Feng; Li, Shan-Shan; Lin, Chu-Hong; Huang, Xing-Jiu; Liu, Wen-Qing
Abstract : A novel Fe 0 @Fe2 MnO4 nanomaterial achieved an ultrasensitive electroanalysis of As(iii ), and it is found that the redox potential of the surficial redox couple determines the improvement of As(iii ) sensitivity. Abstract : A novel zero-valent iron nanomaterial (Fe 0 @Fe2 MnO4 ) was synthesized and achieved an ultrasensitive electrochemical detection of As(iii ). It was found that the enhanced sensitivity is attributed to the surficial catalytic redox couple Fe(ii )/Fe(iii ) induced by Fe 0 of Fe 0 @Fe2 MnO4 . Besides, the catalytic kinetics was modelled and simulated, and the strong influence of the oxidation potential of the catalytic redox species on sensitivity was revealed. By tailoring the surficial atomic and electronic structures of the material, the redox potential can be altered, which can be used for controlling the electro-sensitivity and selectivity in electroanalysis.